2004
DOI: 10.1104/pp.104.047068
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of an Arabidopsis Mutant That Overaccumulates O-Acetyl-l-Ser

Abstract: O-Acetyl-L-Ser (OAS) is a positive regulator for the expression of sulfur (S) deficiency-inducible genes. In this study, through the isolation and analysis of Arabidopsis mutants exhibiting altered expression of S-responsive genes, we identified a thiol reductase as a regulator of the OAS levels. Ethyl methanesulfonate-mutagenized M2 seeds of transgenic Arabidopsis NOB7 carrying a chimeric S-responsive promoter driving the green fluorescent protein gene were screened for mutants with altered levels of green fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 55 publications
3
31
0
1
Order By: Relevance
“…We suggest that the increase in Ser levels in MTX-treated cells was at the origin of the elevation of OAS through an increased activity of Ser acetyltransferase. This assumption is supported by the previous finding that Ser application to Arabidopsis plants increased OAS levels and induced S deficiency response (Ohkama-Ohtsu et al, 2004). Also, in cells treated with MTX and LV, we found that the accumulation of Ser, OAS, and transcripts of the S-responsive gene APR1 was less important and delayed as compared to cells treated with MTX alone (Fig.…”
Section: Folate Depletion Is Associated With a Reorientation Of C1 Unsupporting
confidence: 80%
“…We suggest that the increase in Ser levels in MTX-treated cells was at the origin of the elevation of OAS through an increased activity of Ser acetyltransferase. This assumption is supported by the previous finding that Ser application to Arabidopsis plants increased OAS levels and induced S deficiency response (Ohkama-Ohtsu et al, 2004). Also, in cells treated with MTX and LV, we found that the accumulation of Ser, OAS, and transcripts of the S-responsive gene APR1 was less important and delayed as compared to cells treated with MTX alone (Fig.…”
Section: Folate Depletion Is Associated With a Reorientation Of C1 Unsupporting
confidence: 80%
“…Semi-quantitative RT-PCR was conducted with optimum cycles for each gene. The primer sets for the analyzes genes were as follows: a set for RPT2a was same as described by Sonoda et al; 9) 5 0 -AAGTCAGCGGAGACAGGGAA-3 0 (F) and 5 0 -TAGATGATCCTGATTCGAAAAC-3 0 (R) for RPT5a; a set for Actin8 was same as described by Ohtsu et al 20) Actin8 transcript was used as a reference. Quantitative real-time RT-PCR was performed with SYBER premix exTaq Ò II (Takara) on a Thermal Cycler Dice Ò Real Time System (Takara).…”
Section: Methodsmentioning
confidence: 99%
“…Such proteins should present special characteristics: the redox center of the Arabidopsis NTRs is situated in a groove and is only accessible to proteins with a disulfide bridge on the surface of a small molecule or on an appendage of a large molecule (Dai et al, 1996). To date, such structures have been described only for the thioredoxin superfamily and, more recently, for the g-interferon-inducible thiol reductases (Hastings et al, 2006), with six homologs in the Arabidopsis genome, one of them implicated in high O-acetyl-LSer accumulation (Ohkama-Ohtsu et al, 2004).…”
Section: A Glutathione-dependent Pathway Reduces Type H Thioredoxins mentioning
confidence: 99%